2020
DOI: 10.1016/j.artd.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Travel Distance on Outcomes for Hip Resurfacing Arthroplasty at a High-Volume Center

Abstract: Background: Patients are increasingly traveling greater distances to receive care at high-volume centers. The effect of travel distance on patient-reported outcomes after hip resurfacing arthroplasty has not been described. Methods: Patients undergoing HRA by a single surgeon from January 2007 to April 2018 with minimum 2-year follow-up were reviewed retrospectively. Five hundred ninety-nine patients were identified and divided into 2 cohorts: home-to-hospital distance >100 miles and 100 miles from our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast, Medicare's COE program for bariatric surgery did not affect access to care for nonwhite or rural patients, despite increased travel distances relative to non-Medicare patients, suggesting that each centralization program needs to be evaluated individually for its effects on different demographic populations [25]. One concern with increased travel distances might be an association with increasing complication/readmission rates; however, prior studies have not found a link between travel distance and complications in primary TJA [34,44]. Additionally, increased travel times impose a cost on patients, and for primary TJA, patients were willing to pay an extra USD 11.45 out of pocket to avoid traveling per mile for arthroplasty care, which means patient preferences will need to be further evaluated [42].…”
Section: Effect Of Centralization On Patient Demographic Characteristicsmentioning
confidence: 97%
“…In contrast, Medicare's COE program for bariatric surgery did not affect access to care for nonwhite or rural patients, despite increased travel distances relative to non-Medicare patients, suggesting that each centralization program needs to be evaluated individually for its effects on different demographic populations [25]. One concern with increased travel distances might be an association with increasing complication/readmission rates; however, prior studies have not found a link between travel distance and complications in primary TJA [34,44]. Additionally, increased travel times impose a cost on patients, and for primary TJA, patients were willing to pay an extra USD 11.45 out of pocket to avoid traveling per mile for arthroplasty care, which means patient preferences will need to be further evaluated [42].…”
Section: Effect Of Centralization On Patient Demographic Characteristicsmentioning
confidence: 97%
“…These findings may be representative of patient factors (eg, severity of disease limiting ability to travel long distances for care) or may be associated with the volume or resources of treating facilities (eg, travel needed to reach high-volume, high-quality centers). In contrast to these reports, yet in alignment with findings from this study, several investigations exploring elective orthopedic procedures reported no difference in outcomes according to distance traveled to a tertiary care center . Although it can be hypothesized that patients traveling longer distances may be more committed to their health or have the ability to travel for medical care, and their corresponding habits and behaviors may be responsible for their improved outcomes, this phenomenon is not observed across the entirety of the disease spectrum.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to these reports, yet in alignment with findings from this study, several investigations exploring elective orthopedic procedures reported no difference in outcomes according to distance traveled to a tertiary care center. [17][18][19] Although it can be hypothesized that patients traveling longer distances may be more committed to their health or have the ability to travel for medical care, and their corresponding habits and behaviors may be responsible for their improved outcomes, 10 this phenomenon is not observed across the entirety of the disease spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation